Thanks in advance. $\displaystyle \frac{5x-5}{6} \cdot \frac{x}{x^2-x} = \frac{5x^2-5x}{6x^2-6x} = x^2+x $
Follow Math Help Forum on Facebook and Google+
Nope, I am sorry to say. factor: $\displaystyle \frac{5(x-1)}{6}\cdot\frac{x}{x(x-1)}=\frac{5}{6}$
Originally Posted by Jarod_C Thanks in advance. $\displaystyle \frac{5x-5}{6} \cdot \frac{x}{x^2-x} = \frac{5x^2-5x}{6x^2-6x} = x^2+x $ Your problem can be found here... $\displaystyle \frac{5x^2-5x}{6x^2-6x} = x^2+x $ You took out the coefficients instead of the variables. The end result should be five sixths as Galactus showed you.
View Tag Cloud